(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The exploration of the relationship between language and human perception has been a central focus in cognitive science, attracting scholars from various disciplines including linguistics, psychology, and anthropology. The complexity of proving a direct interconnection between language and thought without substantial evidence has long posed a challenge, as noted by O.A. Kornilov (2003). Within this framework, seminal studies by B. Berlin and P. Kay (1969) have significantly contributed to our understanding of how language shapes perceptual categories, which has profound implications for the field of translation.